(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The study aimed to identify the attitudes of Sultan Qaboos University towards distance learning during the Corona pandemic. The study employed a descriptive method that involves a cross-sectional design. A scale was built to measure attitudes toward distance learning. This scale includes the three components of attitudes: cognitive, emotional, and behavioral. The scale was administered on a sample of (490) undergraduate students affiliated with Sultan Qaboos University during the 2020/2021 academic year, in which distance learning was adopted. The study revealed that undergraduate students’ attitudes towards distance learning were negative. In addition, they expressed negative emotions towards distance learning, communicating their unwillingness and behavioral tendencies to avoid it. Moreover, female undergraduate students expressed more negative attitudes toward distance learning than their male counterparts. Furthermore, the study revealed no effect of college type and study year on attitudes towards distance learning. However, students’ feelings about distance learning in this study and their behavioral tendencies regarding it seem to conflict with their knowledge and information about it. The study concluded that undergraduate students’ experiences with distance learning during the Corona pandemic played a vital role in shaping their negative attitudes towards it. These results call for a comprehensive evaluation process for the university’s e-learning experience.